Effect of a new hand-forearm splint on grip strength, pain, and function in patients with tennis elbow. (June 2016) - Najafi, Mozhgan; Arazpour, Mokhtar; Aminian, Gholamreza; Curran, Sarah; Madani, Seyed Pezhman; Hutchins, Stephen W
Background: While the effectiveness of orthoses prescribed for tennis elbow has been reported in several studies, the effect of how they may limit movements which aggravate this condition has not yet been explored. Objective: The purpose of this study was to evaluate the effect of a new spiral hand-forearm splint that restricts the movement of the wrist and forearm, on grip strength, pain, and function in patients with tennis elbow. Study design: Quasi-experimental design. Methods: A total of 15 patients with tennis elbow (mean age 43 years) took part in this study. The amount of pain, grip force, and function were compared using a visual analog scale, Jamar dynamometer, and the Disability of the Arm, Shoulder, and Hand questionnaire, respectively. This was performed at baseline and repeated after 4 weeks of splint use. Active motion of the forearm was measured by a goniometer. Results: The spiral splint significantly relieved pain and improved function and grip force in patients after 4 weeks of application ( P  < 0.05). Conclusion: The new splint design had a positive effect on the treatment of tennis elbow symptoms which included pain, grip strength, and function. Restriction of rotational movement (e.g. reduction of the supination and pronation of forearm) may have played the main role in this. Clinical relevance: This new splint design may be considered as a new approach in the conservative treatment and rehabilitation of patients with tennis elbow.